Use of floss/interdental brushes is associated with lower risk for new cardiovascular events among patients with coronary heart disease. (14th May 2014) - Reichert, S.; Schlitt, A.; Beschow, V.; Lutze, A.; Lischewski, S.; Seifert, T.; Dudakliewa, T.; Gawe, R.; Werdan, K.; Hofmann, B.; Schaller, H.‐G.; Schulz, S.
Abstract : Background and Objective: Periodontitis has been found to be associated with coronary heart disease (CHD) and stroke. However, only little is known about whether periodontitis and associated confounders are associated with new cardiovascular events among patients with CHD. Material and Methods: A total of 942 inpatients with CHD were examined regarding periodontitis, oral care habits, bacteria in the subgingival biofilm and the expression of interleukin‐(IL)‐6 c. (coding DNA)–174 genotypes (rs 1800793) to determine whether these confounders are associated with new cardiovascular events within a 1‐year follow‐up period. Adjusted hazard ratios (HR) with respect of age, gender, smoking, body mass index, use of aids for interdental hygiene, plaque index, occurrence of severe periodontitis and further internal diseases such as diabetes, hypertension, dyslipoproteinemia, number of missing teeth, serological parameters and IL‐6 genotypes were generated with Cox regression. Results: In all, 941 cardiovascular patients completed the 1‐year follow up and 7.3% of the patients achieved the primary endpoint (myocardial infarction: 2.1%, stroke/transient ischemic attack: 1.8%, cardiovascular deaths: 3.4%). Patients who reported practicing interdental cleaning were younger, less likely to be male or to have severe periodontitis, had a reduced tobacco exposure, had fewer missing teeth, less indices for plaque and bleeding on probing and a significant decreased adjusted risk for new cardiovascular events (HR = 0.2, CI 0.06–0.6, p = 0.01) than those patients with CHD who did not report practicing interdental cleaning. We did not obtain significant increased HR for patients with severe periodontitis (HR = 1.2, CI 0.7–2.1, p = 0.53), carriers of the IL‐6 genotypes GC or CC (HR = 1.4, CI 0.8–2.5, p = 0.24) and did not find a significant association between the number of detected various oral species and the incidence of the combined endpoint (HR = 0.9, CI 0.8–1.01, p = 0.07). Conclusions: These findings suggest that flossing and brushing of interdental spaces might reduce the risk for new cardiovascular events among patients with CHD. The hypothesis that interdental cleaning per se reduces the risk of new cardiovascular events should be examined in an interventional study.